Ontological Core of the Social Concept of Global Constitutionalism: a Socio-Philosophical Analysis of Content and Evolution - Jacek Zalesny; Vitaly Goncharov (International Society of Philosophy and Cosmology, 2019)
This article explores the development of the conceptual foundations of the social concept of global constitutionalism. It is proved that the evolution of ontological principles in global constitutionalism is due to a system of processes: 1) the convergence of neoliberalism and neoconservatism, due to the gradual washing out of the philosophical core in them, its replacement by political technologies that justify the practice of satisfying the interest of political classes and population groups; 2) the formation on a planetary scale of a single global governing class headed by a single system of elites; 3) the formation of a single financial and economic basis for further globalization of socio-political and state-legal development in national states; 4) the formation of a single general goal of the global governing class, which has a purely practical (rational) nature, subject to the logic of preserving power and property in the hands of global governing elites - the preservation and development of the world capitalist system. Thus, global constitutionalism acts as a social concept that justifies the globalization of the socio-political, state-legal, financial and economic structure of national states and societies, filling it with content. It substantiates the position that the social concept of global constitutionalism in the ontological, epistemological, methodological and axiological terms has incorporated the most rational concepts and constructs not only from neoliberal and neoconservative, but also from national socialist (Nazi) and fascist social concepts. Examines the impact on the evolution of the ontological principles of social concept of global constitutionalism content of the ontological principles and other social concepts. It substantiates the position that the ontological perception of the world picture in the framework of the social concept of global constitutionalism as a whole is built on the basis of neoliberalism and neoconservatism that prevailed in the Western world, being the most rational systemic updating of their principles. The goal of research: to investigate the genesis of the ontological principles in global constitutionalism. Subject of research: theoretical content and stages of development of ontological principles in global constitutionalism in relation to its social essence.